The 15-Minute Audition: Translating a Proof of Concept Into a Domain-Specific Screening Device for Mathematical Talent. (July 2017) - Subotnik, Rena F.; Worrell, Frank C.; Olszewski-Kubilius, Paula
In 2011, Subotnik, Olszewski-Kubilius, and Worrell proposed a conceptual model for talent development applicable to all domains. Although grounded in available psychological research, significant questions remain regarding practical applications of each tenet of the model. In this article, we highlight a method of implementing the model's focus on domain-specific abilities. Mathematics was selected as a domain with sufficient literature and importance to serve as the first in a series of proposed explorations into identifying domain-specific abilities. The methodology adapts an identification procedure—that is, audition—commonly used in performance domains (e.g., dance) to determine "drop-dead" abilities needed for successful talent development—in this case, mathematics. Identifying abilities central to potential creative talent in a domain may allow us to move away from relying solely on standardized measures of general ability and academic achievement, especially for the early identification of talent.